Backstage pass for trainers, facilitators, and public speakers : your guide to successful presentations - Jones, Susan J. (Corwin Press, 2006)
A do-it-yourself speaking coach, mentor, and image consultant rolled into one, this humorous book shows how to get your point across and win your audience.